2012
DOI: 10.1248/bpb.b12-00461
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic Function and Mechanism of Ginseng Saponins in Rattus Pancreatic β-Cells

Abstract: Apoptosis is the main form of β-cell death in diabetes. Ginseng has been used as an anti-diabetic herb for several thousand years in Asia with ginsenoside Rg1 and ginsenoside Rb1 as important active ingredients. In this study, we demonstrated ginsenoside Rg1 and Rb1 protect β-cells from high glucose/cytokine-induced pancreatic β-cell apoptosis via inhibiting nitric oxide (NO) production and regulating apoptosis-related genes. Among these genes, Bax, Fas and Caspase-3 gene expressions were up-regulated by high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Therefore, drugs that inhibit cardiomyocyte apoptosis in patients with residual cardiac function may be protective and may delay and inhibit the progression of heart failure. Ginseng, Carthamus tinctorius , and other traditional Chinese medicines and their active ingredients can inhibit cardiomyocyte apoptosis after ischemia [10, 11]. Qin et al have reported that inhibition of cell apoptosis significantly improves heart function in myocardial infarction rabbits [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, drugs that inhibit cardiomyocyte apoptosis in patients with residual cardiac function may be protective and may delay and inhibit the progression of heart failure. Ginseng, Carthamus tinctorius , and other traditional Chinese medicines and their active ingredients can inhibit cardiomyocyte apoptosis after ischemia [10, 11]. Qin et al have reported that inhibition of cell apoptosis significantly improves heart function in myocardial infarction rabbits [12].…”
Section: Introductionmentioning
confidence: 99%
“…As in our previous study, 25 mM glucose was used in this investigation to construct apoptotic cell models with high apoptotic rate and low insulin secretion [38]. Mechanisms of high glucose induced β-cell apoptosis include increasing iNOS expression together with regulation of apoptosis-related gene expressions involved in three pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In consistent with our previous observation, high glucose induced apoptosis via Fas signal pathway and imbalance expression of Bcl-2 versus Bax . The anti-apoptotic gene Bcl-2 expression did not response to high glucose stimulation, whereas pro-apoptotic Bax gene was increased [38], leading to the alteration of the mitochondrial homeostasis, and subsequent activation of apoptosis. In addition, up-regulated expressions of ATF-3 , JNK , p38 and down-regulated expressions of Akt revealed the high glucose induced apoptosis is closely related with ER stress pathway too.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations